Interfacial bioconjugation on emulsion droplet for biosensors. Issue 19 (15th October 2018) - Zhang, Qifan; Scigliano, Anita; Biver, Tarita; Pucci, Andrea; Swager, Timothy M.
Graphical abstract: Abstract: Interfacial bioconjugation methods are developed for intact liquid emulsion droplets. Complex emulsion droplets having internal hydrocarbon and fluorocarbon immiscible structured phases maintain a dynamic interface for controlled interfacial reactivity. The internal morphological change after binding to biomolecules is readily visualized and detected by light transmission, which provides a platform for the formation of inexpensive and portable bio-sensing assays for enzymes, antibodies, nucleic acids and carbohydrates.